Can Mobile-Based Learning Media for Science Materials Influence Junior High School Students' Interest in Learning? Bahasa Inggris - Wachidyastuti; Insih Wilujeng (Postgraduate, University of Mataram, 2024)
Mobile-based learning media is one of the tools that can improve the effectiveness and efficiency of teaching and learning activities. The purpose of this study is to examine the effect of using mobile-based media on junior high school students' interest in learning science subjects. Data were collected through related journals to be reviewed. The method used in this research is the SLR (Systematic Literature Review) method. This research analyzes search results from the Google Scholar database, publish or perish and semantic scholar with a time span of the last 5 years, 2018-2023. Based on the search results, 40 relevant articles were obtained which were then filtered based on the inclusion criteria, 11 accredited national journal articles on SINTA 1 to SINTA 4 were used as primary studies. The results showed that the use of mobile-based media in science learning is very influential to arouse student interest and have an impact on student learning outcomes.